Walter Fähndrich : Musik für Räume. - Schlosshof, Weimar; Weimar 99 Kulturstadt Europas Weimar 1999 (Ostfildern-Ruit : Hatje Cantz Verlag Ostfildern-Ruit, 1999)
Walter Fähndrich has chosen three places - the inner courtyard of the castle, the meander in the Park on the Ilm and the Russian cemetery at Belvedere castle - in order to realize his project for Weimar 99. The three places are connected to each other through a tight time structure ; the respective sunrise and sunset of a day determines the rhythm in which the compositions resound at the various sites. Each site will be defined by an individually developed composition, whereby the music which the Swiss composer creates is formally completely open, undirected, free of reference. Fähndrich relates the freedom of listening to the correspondence between space and music : a listening experience for the promenader, the sounterer, those who take the time and leisure to experience Music for Spaces, in time and space.
Im Rahmen von Licht auf Weimar - Die ephemeren Medien = A project for Light on Weimar - The Ephemeral Media
Duits
Engels
Walter Fähndrich : Musik für Räume / Music for Spaces. Friedhof, Ilmpark, Schlosshof Weimar. Weimar 99 Kulturstadt Europas. 1999
boek
Keywords: Fähndrich, Walter; Weimar